RENEWABLE ENERGY USE IN RASPBERRY PRODUCTION - Subić, Jonel; Kjajić, Nataša (Economics of Agriculture, 2017)
Papers focus is on the economic effects of introducing energy from renewable sources (solar energy) in the raspberry production (mainly for irrigation). Main goal is to assess economic effectiveness of investment in establishing and exploiting raspberry plantation, as well as implementation of required equipment and mechanization, from the point of two investment scenarios. First scenario considers conventional way of raspberry production, compared to raspberry production under mobile solar robotized electric generator. Methodologically, the analysis implies application of a set of methods for dynamic evaluation of investment and methods for evaluation of investments under uncertainty (the net present value, the internal rate of return, the payback period and the break-even point). The result of conducted assessment shows that, apart from ecological beneft, there is high economic justifcation of investment into device used for transfer of renewable into electric energy in raspberry production.